Находка личинок дипилидинды—Joyeuxiella rossicum (Skryabin,1923) Mathevossian, 1963 (Cestoda, Dipylidiidae) — у грызунов на территории СССР - Шарпило, Л.Д. (Вестник зоологии, 1971)
The article is devoted to the first case of finding Joyeuxiella rossicum (Skr j a b i n,
1923) larvae in Muridae rodents.
The larvae were found in the liver of Mus musculus L. caught in Kiev in 1953. The
description and drawing of the larva are given. The finding extends the boundary of the
species areal to the North.